Learning Strategies in English Skills used by Good Language Learners in Millennial Era: A Positive Case Study in Universitas Negeri Makassar - Atmowardoyo, Haryanto; Weda, Sukardi; Sakkir, Geminastiti (ELT Worldwide: Journal of English Language Teaching, 2021)
This article is another part of the research results conducted with the aim of developing a theory of learning English as a foreign language. The other part has been reported in the article entitled Information Technology Used by Good Language Learners in Millennial Era in Solid State Technology Volume 3 Issue 5.           Theory development is carried out by utilizing best practice as a data source. The research question is "What English learning strategies are used by high achievers in the millennial era?". The main questions are translated into 4 (four) questions based on 4 types of language skills: Listening, Speaking, Reading, and Writing. Research subjects were selected based on academic achievement. Subjects were students of the 4th semester of English Department with 20% of the best academic achievement. The selected subjects were 40 students from the English Education Study Program and the English Literature Study Program. They were called as good language learners in Universitas Negeri Makassar.           The instrument used to collect data was a list of open questions consisting of 12 questions. The list of questions was distributed from March to May 2020 via google form to the WhatsApp account number of the research subjects. The collected verbal data were analyzed by using coding.           The results of the study contain descriptions of the types of strategies used by research subjects in improving English listening, speaking, reading, and writing skills. This description also includes the length of time used to improve the four types of English skills.The result shows that, (1) the millennial good language learners’ use a number of language learning strategies to improve their four types of language skills: listening, speaking, reading, and writing. This information is beneficial for ELT teachers, learners, and further researchers for formulating post pandemic language pedagogy.